Analysis of information literacy training at the National University of Lesotho - Lefalatsa, Limakatso (Library and Information Studies Centre (LISC), 2019)
Information literacy skills are a necessity among university students, hence information literacy instructors should keep abreast with the 21st century information literacy curriculum, its delivery and assessment. The study investigated information literacy training and its needs at NUL. The purpose was to investigate information literacy curriculum, delivery and assessment at the National University of Lesotho. Guided by the Association of College and Research Libraries (ACRL) information literacy framework for higher education, the study sought to establish the extent to which the NUL information literacy programme considers ACRL frames or any other standard of relevance. The study adopted a qualitative approach using a phenomenology research design. Data was collected from NUL Subject Librarians through focus group discussions and one on one interview with the Lecturers. Data was generated from structured interview questions; analysed manually and presented in an interpretative form such that participants’ responses were tabulated under subheadings corresponding to the items from the research instruments that were formulated from the research questions. Major findings are that there is no information literacy programme in place hence there is no specific curriculum at NUL, as a result there is also no benchmarking. NUL Subject Librarians take initiative to improvise information literacy content; they use lecture mode and library tours as their predominant mode of information literacy teaching and learning. Although there is a Communication Skills Course meant to assist students with information and communication skills, students struggle to search for information; they are even unable to consult a variety of information sources. The study therefore recommends NUL Library to establish a clear information literacy training programme that is delivered in collaboration with academic staff. It is further recommended that Subject Librarians should contribute to the content of the Communication Skills Course.